Fractionation of Trace Metals between Catchment Soils and Associated Wetland Sediments of Selected Wetlands of Lake Victoria, East Africa - Henry, Leonia; Omutange, Elijah (Journal of Wetlands Ecology, 2010)
The aim of this work was to study the trace metals transfer between soil aquifers and the immediate sediments of the selected wetlands of Lake Victoria. The study covered five trace metals Pb, Cd, Cu, Zn and Mn as these are associated with vehicular traffic and with the combustion of fossil fuels which could both be significant sources of pollution within the wetlands of Lake Victoria basin. Three types of trace metal analyses from various locations of Katonga, Simiyu and Nyando catchments of Lake Victoria were performed: total concentrations, the concentrations in the non-residual fraction and the concentration in the exchangeable fraction. The soil characteristics: texture, pH and organic matter contents, were studied in relation to Cation Exchange Capacity (CEC) to assess the rate of movement of the metals between the soil and the wetland sediments. Eventually, the potential retention and leaching capacity of trace metals within the catchment soils and its possible impact on the composition of the receiving sediments of the wetlands were studied. The comparison between Nyando and Simiyu wetlands showed high variations in the soil characteristics and hence in leaching capacity of the studied metals. In general most areas in Nyando wetland required some measures to improve the CEC of the soil for higher agricultural productivity. Key Words: Trace metals; fractionation; CEC; leaching capacity; soil properties DOI: 10.3126/jowe.v3i0.2222 Journal of Wetlands Ecology, (2009) Vol. 3, pp 68-76